Influence of CAD-CAM diamond bur deterioration on surface roughness and maximum failure load of Y-TZP-based restorations - Corazza, Pedro Henrique; Castro, Humberto Lago de; Feitosa, Sabrina Alves [UNESP]; Kimpara, Estevão Tomomitsu [UNESP]; Bona, Alvaro Della (Mosher &linder, Inc, 2015)
Purpose: To investigate the influence of CAD-CAM diamond bur deterioration on surface roughness (Ra) and maximum failure load (Lf) of Y-TZP-based ceramic (YZ) substructures (SB) veneered with a feldspathic porcelain. Methods: Two sets of burs (B1 and B2) were used to fabricate 30 YZ SB each in a CAD/CAM system (Cerec In Lab). The SB were identified (1-30) according to the milling sequence (MS). SEM images of the burs were recorded before milling, and after milling 15 and 30 SB. The SB Ra was measured. All SB were veneered, cemented onto a fiber reinforced epoxy resin die, and loaded to failure. Specimens from B1 group were cyclic fatigued (106 cycles) before loading to failure. Fractographic analysis was performed. Data were statistically analyzed using Student's t-test, Weibull analysis, Pearson's correlation and ANOVA (alpha=0.05). Results: The mean Ra value of B1 specimens was statistically greater than B2. Weibull modulus of B1 and B2 were statistically similar. The correlation between MS and Lf was not statistically significant for the groups. MS and Ra had significant correlation for both groups (B1: r=-0.514, P=0.015; B2: r=-0.462, P=0.03). Although the visual aspect (SEM) of the burs was similar after 30 millings, the mean Ra values were significantly different after 27 millings for B1 and 24 millings for B2.